Improving turnaround times for HLA-B*27 and HLA-B*57:01 gene testing: a Barts Health NHS Trust quality improvement project - Nathan Proudlove; Emma White; Delordson Kallon (BMJ Open Quality)
Among other tests, Barts Health NHS Trust clinical transplantation laboratory conducts two important gene-detection tests: human leucocyte antigen (HLA)-B*27 (‘B27’, associated with the diagnosis of ankylosing spondylitis) and HLA-B*57:01 (‘B57’, associated with prediction of abacavir hypersensitivity disorder). The turnaround time (TaT) from sample receipt to return of results is important to clinicians and their patients but was not monitored. Furthermore, we anticipated an imminent increase in demand from a forthcoming pathology service merger, together with long-term increases with the rise of personalised genetic medicine.In this quality improvement project, we identified current TaT performance and sources of delay. Over three plan-do-study-act (PDSA) cycles, we tested three change ideas, two involving using IT to remove manual administrative steps and alert us to samples needing progressing; both were retained. The other change involved separating out the targeted tests; we judged this not worthwhile with current demand levels, although something to be re-examined when volumes increase. During the project, we reduced mean TaT from 3.8 to 3.3 days and increased the proportion within our 5-day target from 78% to 100%. These have been sustained (at 3.4 days and 97%) for the 3 months following our PDSA cycles and illustrate that reducing variation can be as impactful as reducing the mean.We conducted this project during the COVID-19 disruption, which reduced demand substantially. We took advantage of this to allow staff to spend time on these improvement activities. Another interesting feature of the work is that during the project, we compared changes in performance on our targeted B27/B57 tests with that on another comparable test as a control, to consider the impact of the general increased attention (the Hawthorne effect). We found that performance on this control also increased comparably, but then fell away after our project finished, while it did not for B27/B57.